An iterative MPD‐CNN structure for massive MIMO detection under correlated noise channels. Issue 12 (1st April 2021) - Zhang, Zufan; Zhang, Di; Yan, Xiaoqin; Gan, Chenquan; Zhu, Qingyi
Abstract: In massive multiple‐input multiple‐output (MIMO) systems, most of the existing detection work mainly assumes that the channel is the additive white Gaussian noise (AWGN). However, this assumption is difficult to apply to practical communication scenarios. To this end, this paper proposes a message passing detection (MPD) algorithm with a convolutional neural network (CNN) (denoted as iterative MPD‐CNN structure) under correlated noise channels, which is helpful to solve the issue of detection performance degradation in non‐ideal AWGN channels. Firstly, the MPD algorithm based on the channel hardening phenomenon is used to initially estimate the transmitted signal, and then the CNN is concatenated to remove the estimation error for obtaining more accurate channel noise, which provides a beneficial noise distribution for the MPD algorithm. Finally, the theoretical analysis and simulation results show that the proposed iterative MPD‐CNN structure can improve the detection performance in conditions of correlated noise channels and fewer antennas. Compared with the traditional MPD algorithm, its detection performance is more superior.